2008
DOI: 10.1258/ijsa.2008.008065
|View full text |Cite
|
Sign up to set email alerts
|

Topical cidofovir for severe warts in a patient affected by AIDS and Hodgkin's lymphoma

Abstract: We describe a 42-year-old man with AIDS and Hodgkin's lymphoma whose severe and recalcitrant cutaneous warts resolved following treatment with local 1% cidofovir. Clinically significant improvements were observed in a two-week period of therapy. In advanced HIV disease complicated by additional haematological malignancy, cutaneous warts may be difficult to treat and present a challenge for the attending physicians. In similar clinical condition topical anti-human papillomavirus therapy may prove to be safe and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Topical cidofovir has been successfully used with negligible risk in children with refractory warts (27). A case report demonstrated that this agent is effective in treating recalcitrant warts in immunocompromised patients (28).…”
Section: Cidofovirmentioning
confidence: 99%
“…Topical cidofovir has been successfully used with negligible risk in children with refractory warts (27). A case report demonstrated that this agent is effective in treating recalcitrant warts in immunocompromised patients (28).…”
Section: Cidofovirmentioning
confidence: 99%
“…128 Topical and intralesional cidofovir has been shown to be successful in the clearance of both genital and cutaneous verrucae, even in patients with AIDS and recurrent, diffuse verrucae. 143,144 Intravenous cidofovir was used in the case of an 11-year-old child with widespread, recalcitrant verrucae. Five cycles of intravenous cidofovir resulted in the clearance of her cutaneous disease, without recurrence.…”
Section: Antimitotic Therapiesmentioning
confidence: 99%
“…Topical cidofovir has been successfully used with minimal risk in children with refractory warts (3). There are reports of safe and efficacious use of cidofovir in solid organ transplant recipients (4), and cidofovir has been shown in case reports to play a role in treating recalcitrant warts in immunocompromised patients, for example, in HIV (5). This is a case report of two brothers with X-SCID who had recalcitrant warts that cleared with topical cidofovir.…”
mentioning
confidence: 99%